EFFECT OF ETHANOLIC EXTRACT OF MIMOSA PUDICA ROOT L. ON ACUTE RESTRAINT STRESS-INDUCED ANXIETY AND DEPRESSION IN SWISS ALBINO MICE - Shashikumara,; C, Prathima; B, Amrutheswari (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The present study is undertaken to study the ameliorative effects of ethanolic extract of Mimosa pudica root (EMPR) on stress-induced anxiety and depressive-like behavior in Swiss albino mice. Methods: The animals were subjected to acute restraint stress (ARS) for 7 days, and on the 8th day after drugs administration, the antianxiety effect was evaluated using elevated plus maze (EPM) test. Antidepressant activity was evaluated by animal despair models-forced swim test and tail suspension test. Phytochemical analysis of the extract was also conducted. Results: EMPR (1000 and 2000 mg/kg) and the combined test groups have shown significant antianxiety effects similar to the standard diazepam as indicated by an improved open arm exploratory behavior in EPM model. EMPR also significantly reduced the immobility time in the animal despair models tested. Conclusion: Results suggest that EMPR possesses significant anxiolytic and antidepressant activity in male Swiss albino mice.